Evaluation Methods in Biomedical Informatics - Friedman, Charles P.; Wyatt, Jeremy (Health Informatics, 2006)
The BMJ said of the first edition of Evaluation Methods in Biomedical Informatics: "A landmark book, which should have a place of honour in the library of anyone seeking a deeper understanding of clinical informatics in general and evaluation in particular." Since the release of the first edition in 1996, it has become an indispensable course textbook and resource to medical informaticians, students of informatics, healthcare administrators, and health services researchers. After four reprints prompted by continuing sales, this new edition incorporates heavily updated and revised material to reflect the changing demands on today's health information technology professional. As information technology takes on an increasingly central role in health care and biomedical research, successful and reliable methods for evaluation become more and more imperative. Evaluation Methods in Biomedical Informatics, Second Edition, is the best resource available to support discussion, development, and implementation of evaluation procedures in these settings. In addition to revision of all material carried over from its predecessor, this Second Edition includes: A new chapter on economic evaluation A completely revised and expanded chapter on qualitative evaluation at the organizational and cultural levels An extensively re-written introduction to the types of studies on biomedical information systems and technologies New scenarios and examples drawing on a wider range of application areas including bioinformatics A Web site accompanies the book and includes further material, clickable links to all Web sites cited in the book, additional links, case studies, and other tools to support evaluators, as well as updates to the book's content. Anyone whose work requires them to design, carry out, understand or critique studies of requirements, usability, impact or side effects of information systems in health and laboratory settings will find this book invaluable. It is written to be directly usable as both a textbook for formal courses and a reference book for researchers and practitioners.